The quantitative effects of climate change and human activity on the vegetation growth in the Yangtze River Basin - Guo, Renjie; Cai, Anning; Chen, Xin (Frontiers in Earth Science, 2023)
Vegetation has changed dramatically in recent years as a result of various disturbances, but the factors influencing vegetation growth vary geographically. We looked into the impact of climate change and human activity on vegetation growth in the Yangtze River Basin (YRB). We characterized vegetation growth in the YRB using gross primary production (GPP) and the leaf area index (LAI), analyzed the relationship between vegetation growth and climate change using the standardized precipitation evapotranspiration index (SPEI), and quantified the relative contribution rate of climate change and human activity to vegetation growth in the YRB by using residual trend method. The findings revealed that: 1) From 2000 to 2018, the YRB showed an increasing trend of temperature (0.03°C yr−1) and precipitation (4.02 mm yr−1) and that the entire area was gradually becoming warmer and wetter; 2) Vegetation growth in the YRB showed a significant increasing trend (GPP: 7.83 g C m−2 yr−2, LAI: 0.02 years‐1). Among them, 87.40% of the YRB showed an increasing trend, primarily in the northern, eastern, and southern parts, while decreasing areas were primarily found in the Yangtze River Delta (YRD) and the YRB’s west region. 3) Vegetation had a significant positive correlation with SPEI in most areas of the YRB, and it was more sensitive to SPEI over a long time scale. The effects of climate change and human activity on vegetation growth in the YRB were spatially heterogeneous, and climate change was the primary driving factors of vegetation change in the YRB (accounting for 61.28%). A large number of grass were converted into forest, crop and urban. Overall, climate change and human activity promoted the growth of vegetation in the middle and upper reaches of YRB (MUYRB) while inhibited the growth of vegetation in the YRD. The findings of this study will contribute to a better understanding of the effects of climate change and human activity on vegetation growth in the YRB, as well as provide a scientific foundation for future ecological restoration in humid and semi-humid areas.